2023
DOI: 10.1002/adfm.202213343
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Damping Composites Enhanced by Yolk–Shell Piezoelectric Damping Mechanism

Abstract: High‐performance damping materials are significant toward reducing vibration and maintaining stability for industrial applications. Herein, a yolk–shell piezoelectric damping mechanism is reported, which can enhance mechanical energy dissipation and improve damping capability. With the addition of yolk–shell particles and carbon nanotube (CNT) conductive network, damping properties of various resin matrices are enhanced with the energy dissipation path of mechanical to electrical to heat energy. Particularly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Previous work has indicated that the introduction of loading path (conductive fillers) would reduce piezoelectric performance while increasing piezoelectric damping. 13 Hence, conventional methods for measuring piezoelectric performance are not feasible like quasi-static meters. We adopted PFM to investigate the enhancement of piezoelectric performance of composites by carbon coating at microscale.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has indicated that the introduction of loading path (conductive fillers) would reduce piezoelectric performance while increasing piezoelectric damping. 13 Hence, conventional methods for measuring piezoelectric performance are not feasible like quasi-static meters. We adopted PFM to investigate the enhancement of piezoelectric performance of composites by carbon coating at microscale.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, a creative load resistance was proposed by Groo et al, 6 in which BaTiO 3 particles were successfully grown on continuous carbon fibers, offering a continuous path to promote electrons produced by piezoceramic rods move, and electric energy dissipated as heat, thus reaffirming that PPCs for damping application has significant potential for exploitation. 13 Even though some research about PPCs with novel structure and outstanding damping behavior has emerged recently, few studies focus on separate damping contributions brought by mechanical friction (or distortion) and piezoelectric effects, not to mention whether piezoelectric behavior of piezoelectric elements would have an effect on the damping capacity of PPCs. Interface optimization of piezoelectric fillers is an effective way to subtly address the issue while maintaining control over variables.…”
Section: ■ Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure–property relationship of adsorbents can provide useful guidance for designing and developing potential adsorbents. , The exploration of high-performance adsorbents is the key to improving the coefficient of performance by adjusting the number and accuracy of identification sites and the pore structure of adsorbents. , On the one hand, ion imprinting technology is used to prepare ion-imprinted polymers (IIPs) with precise size, shape, and function of recognition sites based on enzyme–substrate and antigen–antibody interactions developed in nature to enable specific recognition of target ions in complex environments. , Due to the advantages of simple preparation, fixed hole size, fast adsorption rates, high selectivity, strong regeneration ability, and good environmental stability, they are widely used in solid-phase extraction, membrane separation, and sensors for metal ions . On the other hand, the yolk–shell nanostructures confer good performance as ideal carriers and nanoreactors due to their large void space and specific surface area. In particular, the presence of cavities not only allows maximum exposure of the active site for effective utilization but also accelerates molecular or ion transfer, and the shell acts as a protection against agglomeration and loss of core material. , In addition, magnetic nanorods are regarded as one of the most promising adsorbent carriers because of their synergetic characteristics of self-stirring and magnetic separation, which not only reduce the solubility loss of the adsorbent but also significantly promote the mass transfer and efficiency of the adsorption process. As a consequence, based on these advantages, the construction of IIPs with a yolk–shell nanostructure on the surface of magnetic nanorods will significantly improve the performance of the adsorbent.…”
Section: Introductionmentioning
confidence: 99%